2005
DOI: 10.2106/jbjs.c.01135
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing of Distal Metaphyseal Tibial Fractures

Abstract: Intramedullary nailing is an effective alternative for the treatment of distal metaphyseal tibial fractures. Simple articular extension of the fracture is not a contraindication to intramedullary fixation. Functional outcomes improve with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 45 publications
4
103
0
4
Order By: Relevance
“…The P value using unpaired t -test is <0.0001. In our study, we allowed partial weight bearing only after signs of the union in form of bridging callus on at least three cortices out of four cortices on radiograph and clinically as the absence of tenderness and movement at the fracture site7 which was usually by 6–8 weeks. The majority of the cases, having fulfilling above criteria around 6–8 weeks and were allowed partial weight-bearing on the affected limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P value using unpaired t -test is <0.0001. In our study, we allowed partial weight bearing only after signs of the union in form of bridging callus on at least three cortices out of four cortices on radiograph and clinically as the absence of tenderness and movement at the fracture site7 which was usually by 6–8 weeks. The majority of the cases, having fulfilling above criteria around 6–8 weeks and were allowed partial weight-bearing on the affected limb.…”
Section: Discussionmentioning
confidence: 99%
“…Active range of movements of knee and ankle joint along with quadriceps strengthening exercises were started on the next day of surgery. Weight bearing was started after radiographic assessment showed signs of union as bridging callus in three out of four cortices and clinically as the absence of tenderness and movement at the fracture site 7. This finding suggested the fracture site has sufficiently consolidated so as to allow partial weight bearing which usually occurs by 6–8 weeks.…”
Section: Methodsmentioning
confidence: 98%
“…He concluded that fixation stability of intramedullary nail is not significantly influenced by distal locking screw orientation in response to sagittal, coronal, or rotational forces [13]. On the contrary, Smucker et al found two parallel locking bolts being a better construct than perpendicular locking bolts in their study [14]. …”
Section: Discussionmentioning
confidence: 99%
“…In distal third fractures, fibular plating, one cross screw across fracture site as lag screw, use of large reduction forceps, temporary unicortical plating, percutaneous manipulation with Shanz pins, femoral distracter and cutting the distal few millimeters of nail distal to the distal screw hole to allow two cross locking screws in the distal fragment, have been the supplementary procedures used to achieve the alignment [14–24]. …”
Section: Discussionmentioning
confidence: 99%
“…[2021] Other two studies reported no effect of fibular fixation on the treatment outcome of patients with tibial fractures. [2223]…”
Section: Discussionmentioning
confidence: 99%